Motivational factors controlling flavor preference learning and performance: Effects of preexposure with nutritive and nonnutritive sweeteners - Gil, Marta; de Brugada, Isabel; Hall, Geoffrey (Elsevier B.V., 2022)
In three experiments thirsty rats were given exposure to a sweet solution (saccharin in some experiments, sucrose in others) prior to consuming a compound of the sweet substance and almond flavoring. Preference for that flavor, in a choice test of almond vs. water, was then assessed. In some cases the rats were hungry, in others they were not. When the sweetener used was saccharin, preexposure reduced the magnitude of the preference obtained on test in both hungry and nonhungry rats. When the sweetener was sucrose, preexposure had this effect only when the rats were hungry. The effects produced after preexposure to saccharin are interpreted as being the result of habituation to its sensory features that reduces the ability of these features to engage in subsequent learning. These effects will occur whether the animal is hungry or not. The results for sucrose are interpreted in terms of the fact that it possesses both sensory and nutritional properties, the role of the latter being dependent on the motivational state of subject. It is suggested that the sensory features of sucrose do not undergo habituation, but that an effect of preexposure can be obtained in hungry rats when the source of the learned preference will depend on learning about the nutritive consequences of the sucrose
Keywords: exposure; flavour preference; motivational factors; saccharin; sucrose; Scopus; JCR